Natural Language Processing and Chinese Computing First CCF Conference, NLPCC 2012, Beijing, China, October 31-November 5, 2012. Proceedings - Zhou, Ming.; Zhou, Guodong; Zhao, Dongyan; Liu, Qun.; Zou, Lei.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the First CCF Conference, NLPCC 2012, held in Beijing, China, during October/November, 2012. The 43 revised full papers presented were carefully reviewed and selected from 151 submissions. The papers are organized in topical sections on applications on language computing; fundamentals on language computing; machine translation and multi-lingual information access; NLP for search, ads and social networks; question answering and Web mining.
Applications on language computing -- Fundamentals on language computing -- Machine translation and multi-lingual information access -- NLP for search, ads and social networks -- Question answering -- Web mining.
Keywords: Computer science; Multimedia systems; Text processing (Computer science; Translators (Computer programs).; Computer Science; Language Translation and Linguistics; User Interfaces and Human Computer Interaction; Multimedia Information Systems; Document Preparation and Text Processing; Computer Applications